Operculum ultrastructure in leech cocoons - Rossi, Anthony M.; Saidel, William M.; Marotta, Roberto; Saglam, Naim; Shain, Daniel H. (Wiley-Blackwell, 2013)
ABSTRACT Clitellate annelids (i.e., oligochaetes including leeches) secrete cocoons as part of their normal reproductive cycle. Typically, the cocoon sheath is passed over the head of the leech and sealed at both ends by opercula (i.e., glue-like material secreted by the clitellum). Both the fibrous cocoon wall (CW) and opercula are chemically-related biomaterials that share unusual physiochemical properties, including thermal and chemical resiliency. To explore the underlying morphology of the operculum, we examined cocoons from four leech species (i.e., Myzobdella lugubris, Theromyzon tessulatum, Erpobdella obscura, and Erpobdella punctata) by transmission (TEM) and scanning electron microscopy (SEM). Transmission electron micrographs of all opercula revealed a common, ultrastructural pattern comprising an electron-dense mosaic of ordered polygons that surrounded interspersed cavities. The long axes of cavities were often oriented directionally, suggesting that operculum material is pliable prior to solidification and distorted as a consequence of cocoon deposition. Concomitantly, the operculum permeates jagged edges of the cocoon sheath sealing the cocoon, which provides a mechanically strong CW/operculum boundary. SEM of leech opercula revealed globular nanoparticles comparable to that observed in bioadhesives from disparate animal phyla (e.g., mussel, barnacle, sea star), suggesting a convergent mechanism of bioadhesion among animals. J. Morphol. 274:940-946, 2013. (c) 2013 Wiley Periodicals, Inc.
Keywords: egg case; clitellate; electron microscopy; bioadhesive; opercula